THE SOLAR FLARE OF FEBRUARY 9 OF 1958 - RIVERA TERRAZAS, LUIS; GONZALEZ C, GUILLERMINA (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1967)
Observations of a class 2 solar flare observed on February 9 of 1958 are presented. This flare showed a series of interesting phenomena, among which the filaments associated to the spot group can be mentioned, the shift in the B portion of the flare that
BOL OBS TONAN TACUB
Keywords: SOLAR FLARE, FEBRUARY, 1958; ASTRONOMIA Y ASTROFISICA; SISTEMA SOLAR; ENERGIA SOLAR